Analisis Ekspor Kopi Indonesia - Heppi Syofya (Syntax Corporation, 2023)
In a country's economy, one aspect that must be fulfilled is international trade. International trade is a driving force in achieving an overall economic level to increase the potential of a country. The purpose of this study is to analyze Indonesia's coffee exports in 2012-2021 using quantitative methods with multiple linear regression models. The data in this study comes from the Central Bureau of Statistics and Bank Indonesia. The results showed that the area of plantation land, total coffee production, Indonesian coffee price, GDP per capita, inflation and exchange rate had no significant effect on Indonesian coffee exports. With reference to these results, Indonesian coffee exports are still unable to be driven by research variables which are actually the hope in achieving high export levels. For this reason, policies are needed so that Indonesian coffee exports can compete in quality, price and partner with countries that are the main source of international trade.